STRATEGI PENGEMBANGAN HUTAN TANAMAN RAKYAT (HTR) DI KABUPATEN HALMAHERA SELATAN PROVINSI MALUKU UTARA DENGAN METODE KOMBINASI SWOT-AHP - Rusli Buamona; Hengki D. Walangitan; Johny S. Tasirin (Universitas Sam Ratulangi, 2015)
ABSTRACTFormulation of development strategies Forest Plantation (HTR) in South Halmahera district studied using SWOT and AHP method. A method to collect information about the internal factors (strengths and weaknesses) and external (opportunities and threats). Based on this information in the Forest Plantation development should be determined a strategy as an alternative strategy should be implemented. To determine the best alternative that will be applied in accordance with the purpose of the merger is used SWOT and AHP method for comparing alternatives exist. HTR development strategy include funding, human resource development of farmers, institutional strengthening of farmer groups, utilization of available land, to activate the role of cooperatives, increase the quality and quantity of extension, ensure business certainty,SOP strengthening licensing and promotion.Keywords: HTR, SWOT, AHP